Communicative and Collaborative Aspects in Indonesian Electronic School Book Evaluation Instruments - Safi'i, Imam; Wahdini, Lili (Journal of Education Reseach and Evaluation, 2021)
This study aims to examine the diversity of communicative and collaborative aspects contained in the evaluation instrument in Indonesian BSE. This study uses a qualitative approach by applying the principles of content analysis. The data sources in this study were 541 evaluation instruments spread over eight teaching materials, namely compiling procedural texts, studying explanatory texts, managing information in lectures, studying life in short stories, preparing proposals, designing scientific papers, assessing works through reviews, and performing plays. The collected data were analyzed using research criteria based on the indicators of communicative and collaborative skills found in the Guidelines for Implementing 21st Century Skills in 2013 Curriculum in SMA and published by Dit. PSMA Directorate General of Primary and Secondary Education. The results showed that overall, the evaluation instruments relevant to various communicative competence indicators were 110 questions or 20.33% while the evaluation instruments relevant to various indicators of cooperative competence were 81 questions or 14.97%. This percentage shows that the communicative and collaborative competences in the evaluation instrument in Indonesian BSE have been developed quite well.